Acquired hemophilia A treated with rituximab in a 62-year-old female with rheumatoid arthritis: a case-based review - D. Mohamadzadeh; S. Assar; F. Farsad (PAGEPress Publications, 2023)
Acquired hemophilia A (AHA) is a rare autoimmune disorder with unpredictable hemostasis that is caused by autoantibody formation against coagulation factor VIII. AHA can occur in the context of autoimmune inflammatory rheumatic disorders. Here we report the case of a 62-year-old female with an 11-year history of rheumatoid arthritis (RA) who presented with cutaneous and mucosal bleeding. Activated partial thromboplastin time was prolonged and not corrected by the mixing test. Factor VIII activity was decreased, and the anti-factor VIII antibody was positive. AHA associated with RA was diagnosed. The patient was treated with rituximab 500 mg weekly for 4 doses and prednisolone 10 mg/daily. The patient did not experience bleeding events after treatment, and factor VIII activity and inhibitor normalized. At the end of the article, we discuss similar cases of RA-associated AHA.